From Smart to Surveillance? Ethical Risks of Data-Driven Urban Governance in Smart Cities - Basri, Syahrul (Unihealth Community Research, 2026)
The rapid expansion of smart city initiatives has reshaped urban governance through the extensive use of digital technologies, big data, and artificial intelligence. While these developments promise greater efficiency, sustainability, and improved public services, they also generate significant ethical risks that remain underexplored in both policy and academic debates. This study critically examines the ethical implications of data-driven urban governance by focusing on four key dimensions: privacy and surveillance, social inequality and digital exclusion, power and control dynamics, and environmental sustainability. Using a qualitative critical literature review, this paper synthesizes interdisciplinary research from urban studies, governance, and technology ethics to identify systemic ethical vulnerabilities embedded within smart city frameworks. The findings indicate that pervasive data collection practices increasingly normalize urban surveillance and threaten individual privacy. Furthermore, smart technologies tend to reproduce existing social inequalities by privileging digitally connected populations while marginalizing vulnerable groups. The concentration of data ownership and algorithmic control within governmental and corporate actors reinforces asymmetrical power relations and constrains democratic participation. In addition, the pursuit of technological efficiency often conflicts with environmental sustainability due to increased energy consumption and resource exploitation. This study argues that without a robust ethical governance framework, smart cities risk evolving into technocratic and surveillance-oriented systems. Therefore, integrating ethical principles such as transparency, accountability, inclusivity, and sustainability is essential for ensuring that data-driven urban governance supports social justice and long-term urban resilience.